Sovereign sukuk pricing analysis: do macroeconomic variables matter? - Rahman, Maya Puspa; Duasa, Jarita; Kassim, Salina; Zainudin, Wan Rahini Aznie (IIUM Press, International islamic University Malaysia, 2017)
Development of the global sukuk market has been pioneered by Malaysia with the launch of the first sovereign 5-year global sukuk of US$600 million in 2002. Since then, the sovereign sukuk market has developed rapidly, with sovereign sukuk being issued by the Governments of Turkey, Qatar, United Arab Emirates, Bahrain and Indonesia to name a few. In view that sovereign securities are not totally free from default, there is also a great deal of concern associated with them as some of the issuing countries have experienced major debt servicing problems in the past such as the Greek debt crisis. As such, it is essential to analyze whether the sovereign sukuk yields do reflect the macroeconomic fundamentals of the issuing country. Based on the analysis of five countries in Asia and the Middle East, this study employs panel data from 2006 to 2013 and shows that only the inflation rate is able to explain the movement of sovereign sukuk yields. The insignificance of other macroeconomic variables such as GDP growth and money supply indicate that tagging the economic growth of the issuing country onto the pricing of sovereign sukuk yields may not be feasible at this juncture. Hence, it is concluded that in order to develop a standalone pricing mechanism different from the one used by the conventional bond market, more efforts are needed so that the sukuk market will expand with even more market player participation to create the liquidity needed for it to develop its own pricing mechanism.